2016
DOI: 10.1016/j.physletb.2016.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Relative information entropy in cosmology: The problem of information entanglement

Abstract: The necessary information to distinguish a local inhomogeneous mass density field from its spatial average on a compact domain of the universe can be measured by relative information entropy. The Kullback-Leibler (KL) formula arises very naturally in this context, however, it provides a very complicated way to compute the mutual information between spatially separated but causally connected regions of the universe in a realistic, inhomogeneous model. To circumvent this issue, by considering a parametric extens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Specific models on how to compute the λ parameter value for various gravitational problems are actively investigated; see e.g. [55] for a quantum geometric approach to the black hole problem, and [58] for the case of the problem of information entropy in cosmology. In the latter work, as an effective model, the λ parameter of the Tsallis/Rényi relative entropy has been defined in a geometric way in order to describe the causal connection between a cosmological domain and its surroundings during the cosmic evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific models on how to compute the λ parameter value for various gravitational problems are actively investigated; see e.g. [55] for a quantum geometric approach to the black hole problem, and [58] for the case of the problem of information entropy in cosmology. In the latter work, as an effective model, the λ parameter of the Tsallis/Rényi relative entropy has been defined in a geometric way in order to describe the causal connection between a cosmological domain and its surroundings during the cosmic evolution.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the corresponding Padmanabhan's "holographic equipartition law" [57] can result an effective cosmological constant in the model. Similar considerations have also been applied to describe the relative information entropy measure inside compact domains of an inhomogeneous universe [58], and an explicit geometric model has been proposed to compute the q-parameter of the Rényi entropy in order to measure the effects of the gravitational entanglement problem.…”
Section: Introductionmentioning
confidence: 99%
“…The gravitational entropy which is defined in this way is conjectured to grow in generic situations due to negative feedback of open gravitational systems, which is proved to hold for linear perturbations of an Einstein-de Sitter background model, and exact Lemaître-Tolman models [17]. It has also been show that in the cosmological context the Kullback-Leibler relative information entropy can be well approximated by the Rényi relative entropy [18], and that it can be linked to Weyl curvature [19]. To distinguish this approach from the other, let us denote the entropy defined based on the information entropy as the HBM gravitational entropy and the gravitational entropy that is derived from the Bel-Robinson tensor as the CET gravitational entropy.…”
Section: Introductionmentioning
confidence: 87%
“…Information entropy (Czinner and Mena 2016;Duan 2012;Rao 2006;Tsujimura and Gen 1999;Shannon 1948) represents the amount of information contained in a system state. Information entropy accurately reflects the system complexity variation.…”
Section: Rms Complexity Analysismentioning
confidence: 99%